Test of a moderated mediation model of green team resilience - Islam, Md Asadul; Hassan, Md Mahamudul; Jantan, Amer Hamzah; Rescalvo-Martin, Elisa; Karatepe, Osman M. (Elsevier Ltd, 2026)
Our paper assesses a moderated mediation model of green team resilience (GTR). Pointedly, it investigates: (a) the link between green ambidextrous leadership and GTR; (b) leaders’ green sense of humor as a mediator between green ambidextrous leadership and GTR; (c) market turbulence as a moderator of the impact of green ambidextrous leadership on GTR via green sense of humor. The abovementioned links were tested utilizing the partial least squares structural equation modeling on data collected from 372 hotel employees in Malaysia. The model proposed in our paper was viable. The results suggest that green exploitative and explorative leadership, as the two components of green ambidextrous leadership, foster GTR, and green sense of humor mediates said associations. More importantly, market turbulence strengthens the positive impact of green exploitative leadership on GTR via green sense of humor.